Diagnostic Accuracy of Cadmium Zinc Tellurite (CZT) Detector-Based Dynamic Single Photon Emission Computed Tomography (D-SPECT) Myocardial Perfusion Imaging (MPI) in the Evaluation of Coronary Artery Disease (CAD) - Saleem, Husnain; Muhammad Inamullah Nouman; Zaigham Salim Dar; Muhammad Adil; Raza, Mehdi; Muhammad Atif (Pakistan Armed Forces Medical Journal, 2026)
Objective: To assess the diagnostic accuracy of CZT detector-based dynamic SPECT MPI for detecting coronary artery disease (CAD), using coronary angiography as the reference standard.Study Design: Cross-sectional Observational Study.Place & Duration of Study: Department of Nuclear Cardiology, AFIC/NIHD, Rawalpindi, Pakistan, from Jan to Jun 2024.Methodology: A total of 198 patients who underwent coronary angiography within three months of a D-SPECT MPI were included. Dynamic SPECT MPI was performed using a CZT detector-based camera following 99mTc-Sestamibi injection during rest and stress phases. Stress imaging incorporated Adenosine infusion. Myocardial blood flow (MBF) and myocardial flow reserve (MFR) values were calculated. An MFR value